Enhancement of Responsivity in Solar-Blind UV Detector With Back-Gate MOS Structure Fabricated on β-Ga2O3 Films - Meng, Dongdong D.; Ji, Xueqiang Q.; Wang, Dafang F.; Chen, Zhengwei W. (Frontiers in Materials, 2021)
Monoclinic Ga2O3 (β-Ga2O3) films were grown on Si/SiO2 by using MOCVD. Then, we fabricated the solar-blind photodetector with a back-gate MOS structure. The device exhibited obvious photoresponse under 254-nm UV light illumination, and the photocurrent increased by five orders of magnitude, which could be controlled by VGS. The current generated under dark conditions could also be regulated by VGS and tended to constant when the regulation of VGS was reaching saturation. Meanwhile, VGS was confirmed to have a certain ability to regulate the photocurrent. The present device demonstrated excellent stability and fast response (rise) and recovery (decay) times under the 254-nm light illumination as well as a responsivity of 417.5 A/W, suggesting a valuable application in solar-blind UV photodetectors.